Metagenomics analysis of the virome of 300 concentrates from a Swiss platelet bank. Issue 6 (18th July 2018) - Brito, Francisco; Cordey, Samuel; Delwart, Eric; Deng, Xutao; Tirefort, Diderik; Lemoine‐Chaduc, Coralie; Zdobnov, Evgeny; Lecompte, Thomas; Kaiser, Laurent; Waldvogel‐Abramowski, Sophie; Preynat‐Seauve, Olivier
Abstract : Background and objectives: Platelet concentrates are frequently transfused to patients with reduced immunity. An exhaustive description of their viral content is needed to prevent unwanted infection. Material and methods: To track viral sequences, a shotgun metagenomics approach was used on a bank of 300 platelets concentrates. Sequences were analysed through the diagnostics‐oriented pipeline ezVIR. Results: We only observed viruses commonly described in healthy individuals. Conclusion: Herein is reported the first viral landscape of a platelet concentrates bank.